Quality Analysis of Indonesian Language Test Questions Class VII SMP Negeri 11 Ruteng Using Iteman Programme Version 4.3 - Suharjo, Yunarius Ugi; Sumardi, Vinsensius (Formosa Journal of Sustainable Research, 2024)
The purpose of this study was to describe the validity, reliability, difficulty index, differentiation index, and the effectiveness of distractors on the even semester Indonesian language test questions of class VII SMP Negeri 11 Ruteng, Manggarai Regency in the 2022/2023 academic year using the Iteman version 4.3 programme. The method used was descriptive quantitative. The validity results show that the 40 items of multiple choice questions compiled are valid questions. The reliability results of 40 questions tested on 25 students obtained an Alpha Cronbach score of 0.788. Thus, the question is declared reliable because the amount of the reliability index is more than 0.60. The average index of difficulty (ITK) of all items is 0.433, with 9 questions at the easy level, 10 questions at the medium level, 12 questions at the difficult level, and 9 other questions at the very difficult level. The average index of discriminating power (IDB) is 0.246 with 13 questions declared feasible, 5 questions declared moderate (feasible and do not need to be revised), 7 questions declared good enough (feasible and need to be revised), 15 questions declared unfit. The results of the effectiveness of the distractors showed that 39 of the questions were functioning and 1 question option was not functioning